Motivasi Kerja dan Komunikasi Mempengaruhi Semangat Kerja Karyawan pada Hotel Santika Seminyak - Suwandari, I Gusti Ayu Paramita Kusuma; Trianingrum, Ni Nyoman Nidya; Putri, Komang Shintiya Nita Kristiana (Jurnal Mosaik Hospitaliti, 2025)
The problems at Santika Seminyak Hotel are that employees seem unenthusiastic and only work because of work demands, do not receive wages to employees during overtime, and a lack of promotion also results in decreased work motivation and employee morale. In addition, the communication that occurs is also not good enough, so it cannot be separated from the problem of miscommunication. This study aims to determine the effect of work motivation and communication on morale. The location of this research is Santika Seminyak Hotel. Data collection techniques used are observation, questionnaires, and interviews. The population includes all employees who work at Hotel Santika Seminyak, with a sample of 41 respondents. The data analysis technique used is Descriptive Statistical Analysis, Data Instrument Test, Classical Assumptions, Multiple Linear Regression, t, F, Determination. Based on the results of the study, obtained the results that work motivation has a positive and significant effect on morale, communication has a positive and significant effect on morale, and work motivation and communication have a positive and significant effect on morale. Suggestions that can be given by researchers are that Santika Seminyak Hotel is expected to provide incentives according to the amount of work achieved by employees, provide training to employees, and always provide rewards to increase employee morale.